Influence of Needle-punching Parameters for the Preparation of Polypyrrole-coated Non-woven Composites for Heat Generation - Subhankar Maity; Shivangi Pandey; Alok Kumar (Tekstilec, 2021)
This work deals with the preparation and characterization of electrically conductive needle-punched non-woven composites for heat generation. Electro-conductive non-woven composites were prepared through the in situ chemical polymerization of pyrrole with FeCl3 (oxidant) and p-toluene sulfonic acid (dopant). A two-stage double-bath process was adopted for the in situ chemical polymerization of pyrrole. The effect of parameters such as fibre fineness, needle-punching density and depth of needle punching on a polypyrrole add-on, and surface resistivity were studied by employing the Box-Behnken response surface design. It was observed that fibre fineness was the most influential parameter of the polypyrrole add-on. The lowest surface resistivity of the polypyrrole coated sample (200 g/m2, prepared with a punch density of 200 punch/cm2, a punching depth of 6 mm and fibre fineness of 2.78 dtex) was found to be 9.32 kΩ/□ with a polypyrrole add-on of 47.93%. This non-woven composite demonstrated good electrical conductivity and exhibited Joule’s effect of heat generation. Due to the application of a 30 V DC power supply, the surface temperature of the non-woven composite rose to 55 ºC from a room temperature of 37 ºC. Optical and electron microscopy images of the non-woven composites showed that PPy molecules formed a uniform coating on the non-woven surface. FTIR studies evidenced the coating of PPy on a polyester surface. These coated non-woven composites were highly electrically conductive and practically useful for the fabrication of heating pads for therapeutic use.